The effect of particle size of highland and mare lunar regolith simulants on their printability in vat polymerisation additive manufacturing. Issue 23 (1st December 2022) - Isachenkov, Maxim; Chugunov, Svyatoslav; Smirnov, Andrey; Kholodkova, Anastasia; Akhatov, Iskander; Shishkovsky, Igor
Abstract: Lunar regolith is the most abundant natural resource on Moon's surface. It is the intensively studied prime candidate for in-situ fabrication and repair (ISFR) technologies for future crewed exploration and resource harvesting missions on the Moon. Additive manufacturing with lunar regolith is a promising ISFR method that can be used for sustainable local production of engineering tools and components. This method requires little quantities of extra materials delivered from Earth, but, like many other prospective ISFR technologies, is sensible to the quality of the pre-processed regolith powders that are used as the primary source materials. The evolution of properties of highland and mare lunar regolith simulants concerning grinding-based pre-processing was studied in this work. The effect of regolith grinding was studied for the processes, relevant to stereolithography-based additive manufacturing. Particle size distribution, mean particle size, UV–Vis, XRD and XRF spectra were acquainted from the samples, ground in a ball mill at various grinding times (to different fraction sizes). The photopolymerization efficiency was assessed for lunar simulant-infilled resins prepared from lunar regolith simulants ground with different parameters. It was found that the grinding time of lunar regolith simulants strongly influences their optical properties – the light absorption in the far UV increased by 5.5 times. Based on the measured photo-polymerization depth, the optimal grinding procedure for mare and highland lunar regolith simulants was determined.